AST/ALT ratio is not useful in predicting the degree of fibrosis in chronic viral hepatitis patients. Issue 12 (December 2015) - Eminler, Ahmet Tarik; Ayyildiz, Talat; Irak, Kader; Kiyici, Murat; Gurel, Selim; Dolar, Enver; Gulten, Macit; Nak, Selim G.
Abstract : Background and aim: Noninvasive tests are primarily used for staging hepatic fibrosis in patients with chronic liver disease. In clinical practice, serum aminotransferase levels, coagulation parameters, and platelet count have been used to predict whether or not a patient has cirrhosis. In addition, several studies have evaluated the accuracy of combinations (or ratios) of these measures. The present study aimed to investigate the relationship between five noninvasive models [AST/ALT ratio (AAR), aspartate aminotransferase to platelet ratio index (APRI), Bonacini cirrhosis discriminant score (CDS), age–platelet index (APind), and King's score] and the degree of hepatic fibrosis as determined by biopsy in patients with chronic hepatitis B and C. Patients and methods: A total of 380 patients with viral hepatitis (237 with chronic hepatitis B and 143 with chronic hepatitis C) who were seen at our clinic between January 2005 and January 2011 were retrospectively analyzed. The degree of fibrosis was determined using the Ishak score. Patients with a fibrosis score of 0–2 were considered to have low fibrosis and those with a score between 3 and 6 were considered to have high fibrosis. Five noninvasive models were compared between the groups with low and high fibrosis. Results: There were statistically significant differences between the hepatitis B and C patients with high and low fibrosis with respect to APind (4.49±2.35 vs. 2.41±1.84; P <0.001 in hepatitis B and 4.83±2.25 vs. 2.92±1.88; P <0.001 in hepatitis C), APRI (1.00±1.17 vs. 0.47±0.39; P <0.001 in hepatitis B and 1.01±1.01 vs. 0.41±0.29; P <0.001 in hepatitis C), CDS (4.53±1.90 vs. 3.58±1.30; P <0.001 in hepatitis B and 4.71±2.03 vs. 3.42±1.49; P <0.05 in hepatitis C), and King's score (24.31±3.14 vs. 7.65±6.70; P <0.001 in hepatitis B and 24.82±2.55 vs. 8.33±7.29; P <0.001 in hepatitis C). There were no significant differences in the AAR between the hepatitis B and C patients with high and low fibrosis (0.78±0.31 vs. 0.74±0.34; P =0.082 in hepatitis B and 0.91±0.40 vs. 0.85±0.27; P =0.25 in hepatitis C). The area under the receiver-operating characteristic curve of the APind, APRI, CDS, and King's score in the hepatitis B group were 0.767, 0.710, 0.646, and 0.770, respectively; these values were 0.732, 0.763, 0.677, and 0.783, respectively, in the hepatitis C group. Conclusion: In conclusion, our data suggest that four of the five noninvasive methods evaluated in this study can be used to predict advanced fibrosis in patients with hepatitis B and C. However, there was no significant relationship between the degree of hepatic fibrosis and the AAR score, indicating that AAR is not useful in estimating the fibrosis stage in hepatitis B and C patients.